First geolocator tracks of Swedish red‐necked phalaropes reveal the Scandinavia‐Arabian Sea connection. (30th October 2015) - van Bemmelen, Rob S. A.; Hungar, Johannes; Tulp, Ingrid; Klaassen, Raymond H. G.
Abstract : We studied migration and wintering patterns of a wader with a pelagic lifestyle during the non‐breeding period, the red‐necked phalarope Phalaropus lobatus . Using light‐level geolocation, we obtained three full annual tracks and one autumn migration track of male red‐necked phalaropes caught during breeding in Scandinavia. These tracks confirmed expectations that individuals from the Scandinavian population winter in the Arabian Sea. Migration was accomplished in two to four migration leaps, staging for a few days in the Gulf of Finland (autumn) or the southern Baltic Sea (spring) and for up to a month in or near the Black and Caspian Sea (autumn and spring). In addition, travel speeds suggested that only the flights between the Baltic and Black/Caspian Sea are non‐stop, and thus the birds seem to make additional short stops during the other flights. Stopover time in the Black/Caspian Sea is only 8–10 d in spring but up to 36 d in autumn, which is longer than expected if only used for pre‐migratory fattening to cover the ca 2000 km to the Gulf of Oman. After entering the Arabian Sea via the Gulf of Oman, birds dispersed over the entire presumed winter range. Winter movements appear to correspond to the spatio‐temporal patterns in primary production linked to seasonally changing monsoon winds. These are not only the first tracks of Scandinavian red‐necked phalaropes, but also the first seabird tracks in the Arabian Sea, one of the most productive and dynamic marine areas on the planet.